Long-term bilateral change in pain and sensitivity to high-frequency cutaneous electrical stimulation in healthy subjects depends on stimulus modality: a dermatomal examination - Escobar-Sánchez, Isabel; Ríos-León, Marta; Taylor, Julian (Frontiers in Medicine, 2024)
Introduction Contradictory changes in pain and sensitivity at long-term following cutaneous 100 Hz high frequency stimulation (HFS) have been previously observed. Thus, we aimed to document long-lasting changes in multimodal sensitivity following HFS, and factors influencing them. Methods Long-lasting changes were assessed with mechanical [brush, von Frey filament (588.2 mN)] and thermal [heat (40°C)/cold (25°C)] bedside sensory testing, and electrical TS (0.2 ms single electrical stimuli), at the homotopic (ipsilateral C6 dermatome), adjacent heterotopic (ipsilateral C5 and C7 dermatomes) and contralateral (contralateral C6 dermatomes) dermatomal sites in a single testing session. TS were applied before and after application of 100 Hz HFS at the ipsilateral C6 dermatome. Subjects rated their sensation and pain intensity to TS, and completed questionnaires related to pain descriptors and quality of life. Results Long-lasting changes in mechanical and cold sensitivity was detected up to 45 min after HFS at homotopic C6 dermatome, and a temporary increase in cold sensitivity at 20 min in the contralateral C6 dermatome (p < 0.05). A slow development of bilateral depotentiation to electrical pain TS was also detected from 40 min after HFS (p < 0.05). Higher HFS-induced mechanical and cold sensitivity was identified in women (p < 0.05). Age and quality of life were associated with pain intensity (p < 0.05). Conclusion Long-term unilateral and bilateral changes in sensation and pain following electrical HFS have been found. These findings may suggest a new insight into the development of persistent pain mechanisms. Further studies are now needed.